Twenty-year trends in diagnosis of life-threatening neonatal cardiovascular malformations. Issue 1 (7th June 2007) - Wren, C; Reinhardt, Z; Khawaja, K
Abstract : Background: Infants with cardiovascular malformations are usually asymptomatic at birth. Earlier diagnosis is likely to improve outcome. Objective: To examine trends in the diagnosis of potentially life-threatening cardiovascular malformations. Methods: Ascertainment of all cardiovascular malformations diagnosed in infancy in the resident population of one English health region between 1985 and 2004. Infants with life-threatening cardiovascular malformations were all with hypoplastic left heart, pulmonary atresia with intact ventricular septum, transposition of the great arteries or interruption of the aortic arch; and those dying or undergoing operation within 28 days with coarctation of the aorta, aortic stenosis, pulmonary stenosis, tetralogy of Fallot, pulmonary atresia with ventricular septal defect or total anomalous pulmonary venous connection. Results: Cardiovascular malformations were diagnosed in infancy in 4444 of 690 215 live births (6.4 per 1000) and were potentially life threatening in 669 (15%). Overall, 55 (8%) were recognised prenatally, 416 (62%) postnatally before discharge from hospital, 168 (25%) in living infants after discharge and 30 (5%) after death. Antenatal diagnoses increased from 0 to around 20% and no case was first diagnosed after death in the past 6 years. However, the proportion going home without a diagnosis remains around 25%. Malformations most likely to remain undiagnosed at discharge were coarctation of the aorta (54%), interruption of the aortic arch (44%), aortic valve stenosis (40%) and total anomalous pulmonary venous connection (37%). Conclusions: One in three infants with a potentially life-threatening cardiovascular malformation left hospital undiagnosed. Better early diagnosis is likely to be achieved by further improvements in antenatal diagnosis and more widespread use of routine pulse oximetry.